Integrating AI Technologies into Hotel Businesses: Opportunities and Challenges (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Today, artificial intelligence has become an area of opportunity in the business space. One of such spaces is the sphere of hotel business. This article will look at the capabilities of Artificial Intelligence (AI), the flexibility of its use, the variability and limitations of use, as well as how deeply AI has an impact in these industries.CEOs are increasingly implementing artificial intelligence, into their workflows to simplify and automate data processing, improve operational efficiency and create more opportunities for future innovation. The list of applications of artificial intelligence is extremely wide: from the automation of data processing to the convenient booking of rooms.In addition, AI also facilitates communication between international people. This article examines survey-based research and statistics, the challenges and complexities that companies may face when using AI. To ensure responsible and effective implementation, of artificial intelligence, organizations must overcome these challenges. With the growth of AI technologies and the expansion of customization and accessibility, the future of AI integration promises to be dynamic.